Endangered Ganges River Dolphin Platanista gangetica gangetica sighted in Rapti river, Balrampur district, Uttar Pradesh, India - Maurya, Kamlesh K.; Hasan, Dabeer; Gupta, Mudit (Journal of the Bombay Natural History Society (JBNHS), 2014)
No Abstract.